2018
DOI: 10.1167/iovs.17-22855
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell–Derived Small Extracellular Vesicles Promote Neuroprotection in Rodent Models of Glaucoma

Abstract: PurposeTo investigate the benefit of bone marrow mesenchymal stem cell (BMSC)-derived small extracellular vesicles (sEV) as an intravitreal (ivit) therapy in two rat models of glaucoma and to determine and identify candidate miRNA involved in the mechanism.MethodssEV were isolated from human BMSC and fibroblasts and ivit injected into adult rats after induction of elevated IOP. IOP was elevated using either intracameral injection of microbeads or laser photocoagulation of circumferential limbal vessels and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
108
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 52 publications
4
108
1
Order By: Relevance
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
“…Wang, Ma, et al, 2018), DDD (Ahn et al, 2015;Beeravolu et al, 2018;Pereira et al, 2016;Perez-Cruet et al, 2018), MS (Harris et al, 2018;Nasri et al, 2018;Planchon et al, 2018), PD (Jamali et al, 2018;H. Kim, Lee, et al, 2018), and RDD (Mead, Amaral, & Tomarev, 2018), as summarized in Table 2.…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
“…Exosomes were characterized via Western blot by their positive staining for the exosome markers Syntenin 1 and CD63 and negative staining for high/lowdensity lipoprotein markers ApoA1 and ApoB. 24 Briefly, exosomes were lysed in passive lysis buffer (Promega, Madison, WI, USA; #E1531) and protein samples (20 μg) were separated on 4% to 12% Bis-Tris protein gels at 150 V for 40 minutes. After transfer to polyvinylidene fluoride membranes and blocking in 10% Western blot blocking buffer (Roche, Basel, Switzerland) in Tris-buffered saline (TBS), proteins were stained overnight in primary antibody (Table) diluted in TBS.…”
Section: Exosome Isolationmentioning
confidence: 99%
“…Densitometry of Western blot bands was analyzed using ImageJ software (National Institutes of Health, Bethesda, MD, USA) as previously reported. 24 All exosomes samples used in the study comprised exosomes pooled from three MSC donors.…”
Section: Exosome Isolationmentioning
confidence: 99%
See 1 more Smart Citation